Przygotowanie do zawodu nauczycieli w świetle raportu NIK i sporu o awans naukowy z dydaktyk przedmiotowych - Śliwerski, Bogusław (Wydawnictwo Naukowe UAM, 2017)
The core idea of the paper’s analysis is the incoherent school and academic government authority’s politics and the chaos caused by it in the process of educating future teachers of school subjects in general education and vocational training (general and mass one) in Poland. The author stresses the role and importance of subject teaching (detailed/specialized teaching) in relation to general teaching and models of vocational teachers’/academic education in contemporary tertiary education.
Vocational Preparation for the Teaching Profession in Light of the Supreme Chamber of Audit Report and of the Dispute About ScientificPromotion in School Subject Teaching
Keywords: didactics; subject/school didactics (detailed one); teacher; vocational preparation; teacher qualification